H. BOTEV’S “HADZHI DIMITAR” POETIC TRANSLATIONS: A COMPARATIVE STUDY (Philological Studies, 2019)
The article considers the Russian and English translations of Bulgarian poet Hristo Botev’s ballad “Hadzhi Dimitar”. It aims to compare the original text to its translations as well as several translations to each another in order to identify linguistic and expressive means.
Keywords: Hristo Botev, Hadzhi Dimitar, ballad, poetic translation, expressive language means